Percutaneous cholecystostomy: a nonsurgical therapeutic option for acute cholecystitis in high-risk and critically ill patients - Dabus, Guilherme de Castro (2003)
Percutaneous cholecystostomy offers a potentially important type of therapy for critically ill patients with acute cholecystitis who present high risk when undergoing laparotomy or laparoscopy under general anesthesia. It offers a distinct advantage for these kinds of patients by avoiding the risks of the surgical intervention. Percutaneous cholecystostomy is a safe and effective minimally invasive procedure with a high success rate and low procedurerelated complications. It should be considered not only in temporary management of calculous cholecystitis, but also in definitive treatment in cases of acalculous cholecystitis.